Diversidade e composição funcional de algas fitoplanctônicas e perifíticas para o aprimoramento agroecológicos em lavouras de arroz e tanques de peixes em um povoado de Arari- MA - Souza, Rafaella Cristine de (2015)
The objective of this study was to verify how ecological understanding of planktonic communities could reflect or contribute to the use of nitrogen fertilizer in rice fields and fish breeding ponds in the village of Arraial, in the Baixada Maranhense. For this, samples were collected according to the agricultural calendar, and physical-chemical analysis of water were obtained with multiparameter probes for measuring temperature, pH, dissolved oxygen, conductivity, ammonium and nitrate; plus made repeated samplings of phytoplankton for each tank in the refuge and rice field, and removed stalks of rice fields. Qualitative and quantitative analysis of phytoplankton and periphyton, taxonomic, functional and indexes data determination, were made. The phytoplankton community was dominated by Euglenoids, and the species Trachelomonas volvocina (Ehrenberg) Ehrenberg the most frequent, while cyanobacteria kept low density with little variation during cultivation in the nursery. In periphyton, the most common species belong to Bacillariophyta group. The taxon of cyanobacteria present in both, phytoplankton and periphyton, do not show up structures responsible for nitrogen fixation, indicating that the increase in nutrient content due to the nitrogen fertilization does not favor the formation of these structures, however, there are no toxins affecting fish activity. From functional groups, the group W2, or inhabitants of the mesotrophic shallow lakes bottom, is the most abundant in phytoplankton, and in periphyton, the planners R or ruderals